Prostaglandin E2 depresses GABA release onto parvocellular neuroendocrine neurones in the paraventricular nucleus of the hypothalamus via presynaptic receptors. (14th October 2018) - Khazaeipool, Zahra; Wiederman, Meagan; Inoue, Wataru
Abstract : Inflammation‐induced activation of the hypothalamic‐pituitary‐adrenal (HPA) axis and the ensuing release of anti‐inflammatory glucocorticoids are critical for the fine‐tuning of the inflammatory response. This immune‐induced neuroendocrine response is in large part mediated by prostaglandin E2 (PGE2 ), the central actions of which ultimately translate into the excitation of parvocellular neuroendocrine cells (PNCs) in the hypothalamic paraventricular nucleus. However, the neuronal mechanisms by which PGE2 excites PNCs remain incompletely understood. In the present study, we report that PGE2 potently depresses GABAergic inhibitory synaptic transmission onto PNCs. Using whole‐cell patch clamp recordings obtained from PNCs in ex vivo hypothalamic slices from rats, we found that bath application of PGE2 (0.01‐100 μmol L ‐1 ) concentration‐dependently decreased the amplitude of evoked inhibitory postsynaptic currents (eIPSCs) with maximum effects at 10 μmol L ‐1 . The PGE2 ‐mediated depression of eIPSCs had a rapid onset and was long‐lasting, and also was accompanied by an increase in paired pulse ratio. In addition, PGE2 decreased the frequency but not the amplitude of both spontaneous IPSCs and miniature IPSCs. These results collectively indicate that PGE2 acts at a presynaptic locus to decrease the probability of GABA release. Using pharmacological approaches, we also demonstrated that the EP3 subtype of the PGE2 receptor mediated the actions of PGE2 on GABA synapses. Taken together, our results show that PGE2, via actions of presynaptic EP3 receptors, potently depresses GABA release onto PNCs, providing a plausible mechanism for the disinhibition of HPA axis output during inflammation.